Formulation and evaluation of a bioadhesive patch for buccal delivery of tizanidine - Mohamed S. Pendekal; Pramod K. Tegginamat (Elsevier, 2012)
Tizanidine hydrochloride (THCl) is an antispasmodic agent which undergoes extensive first pass metabolism making it a possible candidate for buccal delivery. The aim of this study was to prepare a monolayered buccal patch containing THCl using the emulsification solvent evaporation method. Fourteen formulations were prepared using the polymers Eudragit® RS 100 or Eudragit® RL 100 and chitosan. Polymer solutions in acetone were combined with a THCl aqueous solution (in some cases containing chitosan) by homogenization at 9000 rpm for 2 min in the presence of triethyl citrate as plasticizer and cast in novel Teflon molds. Physicochemical properties such as film thickness, in vitro drug release and in vitro mucoadhesion were evaluated after which permeation across sheep buccal mucosa was examined in terms of flux and lag time. Formulations prepared using a Eudragit® polymer alone exhibited satisfactory physicomechanical properties but lacked a gradual in vitro drug release pattern. Incorporation of chitosan into formulations resulted in the formation of a porous structure which did exhibit gradual release of drug. In conclusion, THCl can be delivered by a buccal patch formulated as a blend of Eudragit® and chitosan, the latter being necessary to achieve gradual drug release.